The effcet of annulus fibrosus suture combined with percutaneous transforaminal endoscopic discectomy on obese patients with lumbar disc herniation - Leyu Zhao; Qi Yan; Lijie Yuan; Tianyi Wu; Yun Teng; Junjie Niu; Dawei Song; Jinning Wang; Xiao Sun; Rui Chen; Xianggu Zhong; Jiarong Li; et al. (Frontiers in Pain Research)
BackgroundLumbar disc herniation (LDH) is a prevalent degenerative disc disorder frequently resulting in lumbar and leg pain. Obese patients with LDH often encounter the scenario where the disc herniation is not completely resolved in the short term following percutaneous transforaminal endoscopic discectomy (PTED), necessitating subsequent surgical intervention, or where long-term reherniation occurs post-procedure. Currently, the literature provides little information regarding the application of annulus fibrosus suture (AFS) as a supplementary measure to PTED for diminishing the recurrence of disc herniation. Our aim was to evaluate the short-term and long-term therapeutic outcomes of combining PTED with AFS, with a particular focus on the impact of AFS on the recurrence rate of disc herniation following PTED.MethodsWe recruited 23 obese patients with single-level LDH diagnosed between December 2021 and December 2023. All patients successfully underwent PTED in conjunction with AFS and the postoperative follow-up. We collected and analyzed data related to baseline parameters, disc degeneration grading, clinical effectiveness, surgery-related factors, lumbar spine function, pain severity, quality of life, and adverse prognosis events.ResultsCompared with preoperative assessments, all patients exhibited significant improvements in Visual Analog Scale for leg pain (VAS-LP), Oswestry Disability Index (ODI), and Japanese Orthopaedic Association (JOA) scores (P < 0.05). During the short-term follow-up period, no patient required a secondary conventional microdiscectomy due to severe complications. At the one-year follow-up, no patient experienced significant recurrent radicular leg pain that would raise suspicion of LDH recurrence. However, when PTED was combined with AFS, the improvement in Visual Analog Scale for back pain (VAS-BP) was relatively less pronounced.ConclusionsThe synergy of PTED and AFS seems to be a comparatively safe and efficacious approach for treating LDH in obese patients. AFS reduces the incidence of long-term recurrent leg pain, which may in turn reduce the probability of LDH recurrence after PTED. Consequently, AFS should be regarded as an efficacious supplementary procedure to PTED, adept at efficiently reducing the recurrence rate in obese individuals with LDH.